2020
DOI: 10.1002/essoar.10503569.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation of the record Arctic stratospheric ozone depletion in 2020

Abstract: It is well established that the Antarctic ozone hole (Farman et al., 1985;Jones & Shanklin, 1995) is caused by chemical ozone depletion in austral spring through catalytic cycles driven by chlorine and bromine compounds (e.g., Solomon, 1999;WMO, 2018). For these cycles to run efficiently, chlorine needs to be activated from the reservoir compounds HCl and ClONO 2 by heterogeneous reactions. These heterogeneous reactions only take place at low temperatures typically present in polar winter and spring, occurring… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
8
9
0
Order By: Relevance
“…(As explained in the SI, the vortex‐averaged descent methods give slightly lower estimates than Match because they may be more affected by dilution of the chemical loss signature near the vortex edge.) Record‐low springtime O 3 at lower altitudes in 2020 than in 2011 is consistent with evidence of record‐low total column O 3 (Grooß & Müller, 2020; Wohltmann et al., 2020) and anomalously high surface ultraviolet in 2020 (Bernhard et al., 2020). Large interannual variability in meteorological conditions in the Arctic stratosphere (which led to the exceptionally strong and long‐lived polar vortex in 2019/2020) may yet result in more extreme Arctic O 3 loss in future years while stratospheric chlorine loading remains high: For instance, 2015/2016 still stands out as the coldest Arctic winter with most denitrification and dehydration—if conditions such as those commenced as early in some future year and lasted as late as in 2019/2020, and the vortex remained well‐isolated, then greater O 3 depletion could occur.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…(As explained in the SI, the vortex‐averaged descent methods give slightly lower estimates than Match because they may be more affected by dilution of the chemical loss signature near the vortex edge.) Record‐low springtime O 3 at lower altitudes in 2020 than in 2011 is consistent with evidence of record‐low total column O 3 (Grooß & Müller, 2020; Wohltmann et al., 2020) and anomalously high surface ultraviolet in 2020 (Bernhard et al., 2020). Large interannual variability in meteorological conditions in the Arctic stratosphere (which led to the exceptionally strong and long‐lived polar vortex in 2019/2020) may yet result in more extreme Arctic O 3 loss in future years while stratospheric chlorine loading remains high: For instance, 2015/2016 still stands out as the coldest Arctic winter with most denitrification and dehydration—if conditions such as those commenced as early in some future year and lasted as late as in 2019/2020, and the vortex remained well‐isolated, then greater O 3 depletion could occur.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, HCl production was highly favored inside the persistently cold, strongly denitrified, and ozone-depleted Arctic vortex in spring 2020. Atmospheric Chemistry Experiment-Fourier Transform Spectrometer ClONO 2 data (Boone et al, 2013) ( Figure S6 and Text S4) and model results (Grooß & Müller, 2020) are consistent with this picture.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Stratospheric ozone values over large parts of the Arctic reached record low values in March and April 2020 (Manney et al, 2020) with ozone severely depleted between mid-March and mid-April 2020 when ozonesondes observed minimum mixing ratios of 0.1-0.2 ppm around 17-19 km (Wohltmann et al, 2020), lower than observed in any previous year. Model simulations and evaluation against MLS data by Groß and Müller (2020) also confirmed these findings. The last time similarly low ozone columns were observed over the Arctic was during boreal spring 2011 (Manney et al, 2011) and 1997 (Newman et al, 1997).…”
Section: Introductionsupporting
confidence: 54%
“…(2020, published in this special collection) use observations of relevant chemical species from the Aura Microwave Limb Sounder to illustrate the chemical and transport processes leading to exceptional chemical ozone loss and record low ozone by spring 2020. Other studies presently submitted for this special collection and elsewhere further explore the detailed evolution of ozone during the season using a variety of measurements and models (Dameris et al, 2020; Grooß & Müller, 2020; Inness et al, 2020; Wohltmann et al, 2020), and more are in preparation. Were there downstream impacts related to the strong vortex, ozone deficit, and persistent positive tropospheric AO events? The strong polar vortex, low ozone, and positive AO events that occurred in the late winter/early spring of 2020 were each record‐breaking on seasonal time scales, and as a result, there is a possibility they had farther‐reaching consequences.…”
Section: Discussionmentioning
confidence: 99%